Marital Challenges of Infertile Couples: A Phenomenological Study - Ebrahimi, Marziyeh; Mohsenzade, Farshad; Zahrakar, Kianoush (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study aimed to investigate and determine the marital challenges of infertile couples. Methods: The research had a qualitative method with a phenomenological approach, and its scope consisted of infertile women and men who visited Royan Institute and the Department of Family Counseling and Social Work for advanced infertility treatment. The researcher used a purposive sampling method and semi-structured interviews with 15 couples and analyzed the obtained data based on Colaizzi's practical metho. Results: The research identified 27 subcategories by examining and categorizing the descriptive codes obtained from the interviews, and classified them into six main concepts, namely the challenges in decision-making and acceptance of treatment, challenges related to actions and reactions of the family and acquaintances, concern for cultural and social non-acceptance and religious concerns, the concerns caused by the possibility of physical, mental, and behavioral deficiencies of children, the challenges affecting the marital life, and the economic challenges of infertility treatment, according to their semantic similarity and affinity. Conclusion: The themes extracted indicated that infertility could affect infertile couples' entire life. The greater use of midwifery and psychological counseling services for infertile couples and their acquaintances in infertility treatment centers seems helpful for these couples.